Prawo i etyka w medycyniePatients’ opinions on corruption in the national health service in Poland. Legal aspects of corruption in Poland - Wroński, Konrad; Bocian, Roman; Depta, Adam (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Background: Corruption has been around for thousands of years and anywhere it appears it affects badly the economy and the idea of democracy. According to the law, corruption means offering, handing, demanding, or receiving by any person, directly or indirectly, any undue assets, personal property or other benefits, for themselves or any other person, as well as accepting an offer or a promise of such gains in return for an action or omission when holding a public office, or in the course of conducting business. Aim: The aim of this research was to learn the patients’ opinions about corruption in the National Health Service. Material and methods: A group of 300 patients staying in the Pirogow Hospital in Łódź was requested to fill in a survey prepared by the authors, in which instruments were applied to examine patients’ opinions about corruption in the National Health Service. The necessary calculations were done by means of the followings packets: STATISTICA 7.1 and EXCEL 2008. Results: The survey reveals that 294 (98.0%) respondents have never met with a suggestion or inducement on the part of the doctor to hand in a bribe (money or an expensive object) in order to be admitted to hospital, to be treated, to be operated on or to consult the doctor. Out of 300 respondents, 6 (2.0%) did not remember whether they had ever heard such a suggestion. None of the patients were persuaded to hand in a bribe in order to be admitted to hospital, to be treated, to be operated on or to consult the specialist. According to the research, 157 (52.33%) patients stated that the problem of corruption in the National Health Service was insignificant, 25 (8.33%) patients answered that the problem was petty, whereas 118 (39.34%) respondents declared that it was a marginal problem. None of the patients admitted that corruption in the National Health Service establishments posed a major or grave problem. In the survey, 281 (93.67%) respondents concluded that within the last 3 years corruption in the National Health Service had practically been disposed and ceased to exist. Among 300 respondents, 3 (1.00%) of them stated that in the last 3 years corruption had been decre-asing, whereas 16 (5.33%) patients had no view on this subject. Conclusions: Corruption is a crime which contributes to undermining the idea of democracy, abiding by the law and, what is more, it hinders the free market economy. The wrongdoer is prosecuted ex officio and liable to severe punishment. The research conducted by the authors shows that these days corruption is a marginal problem in the Polish National Health Service. What seems to be the only chance to completely eradicate corruption from the National Health Service establishments is creating a free market of medical services (devoid of the limits defined by the National Health Fund), as well as privatizing hospitals the way it is happening in the developed countries in the European Union and in the United States of America.